Exploring Sustainability in Hospitality Industry from a Marketing Lens: A Systematic Literature Review - Tongyon, Rattiyaphon; Leenanithikul, Oraphan (Journal of International Studies, Prince of Songkla University, 2024)
This systematic literature review examines 43 articles on sustainable marketing within the hospitality industry, sourcing from the SCOPUS database published between 2019 and 2023. The study utilized an integrative review approach, revealing three main findings. Firstly, it highlights various dimensions such as Sustainable Marketing, Social and Cultural Notions, Green Consumers, and Entrepreneurial Marketing in the hospitality industry, emphasizing a relative lack of attention to Green Marketing and Corporate Social Responsibility despite their impact on company performance. Secondly, the research identifies a pervasive absence of universally recognized definitions for sustainability in marketing and consumer behaviour of the hospitality industry, leading to the proposal of a comprehensive term, "sustainability-motivated marketing." Lastly, the study not only organizes existing research but also elucidates future research directions, emphasizing the interdependence of sustainable marketing with entrepreneurship, customer-centric sustainability, and the role of public policy in the hospitality industry